Bio-Inspired Design of Lightweight Metal Structure Based on Microstructure of Fully Ripe Loofah - P. Lei, Yong; Wang, Hui; H. Qin, Qing (Recent Patents on Materials Science, 2015)
It is well known that a naturally matured loofah has some distinct inherent properties including extremely low density and high absorbability, due to its unique fibrous microstructure and macro-cellular architecture including the spatial configuration of voids and solids. In this paper, we focus on patents and literature related to the development of a three-dimensional (3D) lightweight metallic structure by means of a design bio-inspired by the cellular architecture of a fully ripe loofah. To simplify the design, the cellular architecture of the loofah is assumed to be a two-layered open-cell foam structure, and each layer is a porous shell wall. The two layers are connected by three porous radial plates. With this simplification, a lightweight metallic structure with hexagonal pores is developed that achieves the desired balance of weight and mechanical properties. The resulting metallic structure has low density (190.39 kilograms per cubic meter) and the Young’s modulus is estimated by compressive testing using a finite element technique.
Keywords: finite element